Avaliação de matriz de sílica modificada com óxidos mistos dispersos como sorvente na pré-concentração e especiação de íons metálicos usando sistema FIA-FAAS - Lima, Giovana de Fátima (2012)
The present study describes the analytical performance of on-line preconcentration systems using modified silica prepared by sol-gel as sorbent in the extraction/speciation metals, employed flow injection analysis and detection by Flame Atomic Absorption Spectrometry (FAAS). Materials were characterized by FTIR, EDXRF, SEM, EDS, XRD, SBET and EPR. The experimental parameters were studied by multivariate analysis using factorial design, Doehlert design and desirability function. In Chapter I, it was employed a new adsorbent, containing manganese oxide particles dispersed in a silica matrix (SiO2/Mn3O4) to improve the detectability of FAAS for Cd2+ determination. The analytical features were obtained: linear responses in the range of 1.0-50.0 g L-1 (r = 0.9968), the detection (LOD) and quantification limits (LOQ) of 0.20 and 0.68 g L-1,respectively, preconcentration factor (PF) of 39.3, concentration efficiency (CE) of 19.7 min-1, consumption index (CI) of 0.51 mL, and analytical frequency (AF) of 20 h-1. The Chapter II, describes the analytical performance of the hybrid material (SiO2/Al2O3/TiO2) as an adsorbent for Cu2+ enrichment. LOD and LOQ of 0.46 and 1.43 μg L−1, respectively, and linear analytical curve from 5.0 up to 245.0 μg L-1 (r = 0.999), were achieved. Besides, the following parameters were calculated: PF of 49.05, CI of 18.9 min-1, IC of 0.26 mL and AF of 23 h-1. Finally, in Chapter III, the on-line preconcentration system using two minicolumns containing SiO2/Al2O3/TiO2 e SiO2/3-(2-aminoethylamino)propyltrimetho -xysilane (SiO2/AAPTS) was proposed for sequential preconcentration/speciation of Cr3+ and Cr6+ and determination by FAAS. The LOD and LOQ were 0.66 and 2.21 μg L-1 for Cr3+ with a linear analytical curve from 10.0-375 μg L-1 (r = 0.9981). PF, CI, CE and FA were 17.62, 1.13 ml, 6.2 min-1 and 21 measures h-1, respectively. For Cr6+ the LOD and LOQ were 0.27 and 0.93 μg L-1 with a linear analytical curve from 10.0 - 375 μg L-1 (r = 0.9993). The PF, CI, CE and FE were 32.98, 0.6 ml, 11.54 min-1 and 21 measures h-1, respectively. The accuracy of the preconcentration methods was checked using analysis of certified reference materials (CRM).